Sentinel Modular Program for Propensity Score–Matched Cohort Analyses: Application to Glyburide, Glipizide, and Serious Hypoglycemia. Issue 6 (November 2017) - Zhou, Meijia; Wang, Shirley V.; Leonard, Charles E.; Gagne, Joshua J.; Fuller, Candace; Hampp, Christian; Archdeacon, Patrick; Toh, Sengwee; Iyer, Aarthi; Woodworth, Tiffany Siu; Cavagnaro, Elizabeth; Panozzo, Catherine A.; et al.
Abstract : Sentinel is a program sponsored by the US Food and Drug Administration to monitor the safety of medical products. We conducted a cohort assessment to evaluate the ability of the Sentinel Propensity Score Matching Tool to reproduce in an expedited fashion the known association between glyburide (vs. glipizide) and serious hypoglycemia. Thirteen data partners who contribute to the Sentinel Distributed Database participated in this analysis. A pretested and customizable analytic program was run at each individual site. De-identified summary results from each data partner were returned and aggregated at the Sentinel Operations Center. We identified a total of 198, 550 and 379, 507 new users of glyburide and glipizide, respectively. The incidence of emergency department visits and hospital admissions for serious hypoglycemia was 19 per 1000 person-years (95% confidence interval = 17.9, 19.7) for glyburide users and 22 (21.6, 22.7) for glipizide users. In cohorts matched by propensity score based on predefined variables, the hazard ratio (HR) for glyburide was 1.36 (1.24, 1.49) versus glipizide. In cohorts matched on a high-dimensional propensity score based on empirically selected variables, for which the program ran to completion in five data partners, the HR was 1.49 (1.31, 1.70). In cohorts matched on propensity scores based on both predefined and empirically selected variables via the high-dimensional propensity score algorithm (the same five data partners), the HR was 1.51 (1.32, 1.71). These findings are consistent with the literature, and demonstrate the ability of the Sentinel Propensity Score Matching Tool to reproduce this known association in an expedited fashion. See video abstract at, http://links.lww.com/EDE/B275 . Abstract : Supplemental Digital Content is available in the text.